S* control chart in screw quality assessment - Sharif, Shamshuritawati; Ismail, Suzilah; Omar, Zurni (Research India Publications, 2017)
Quality control chart is a powerful tool in assessing quality of products and services. The assembled of control chart involves two phases. The first phase function as the quality standard reference which consist of well behave samples that are within the control limit. The second phase is the real samples that need to be quality tested. In this study we constructed S* control chart based on the two phases using screws data. The advantage of this chart is fulfilling the requirement of high dimensional data set where the number of dimensions is more than the number of sample sizes (p > n) as displays in screw. The samples taken involved only three screws (n = 3) but seven variables (p = 7) measuring the quality of the screws. S* control chart was successfully constructed and able to act as warning signals in detecting defects screw.